2017
DOI: 10.1589/jpts.29.2126
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intervention implemented by trained volunteers improves health-related quality of life among Japanese community-dwelling older females: an intervention study

Abstract: [Purpose] This study aimed to evaluate the sustainability and efficacy of exercise intervention, as implemented by professionally trained volunteers, on the health-related quality of life among Japanese community-dwelling older females. [Subjects and Methods] We conducted a non-randomized observational prospective study of a six-month exercise intervention delivered by volunteers or health professionals. Health-related quality of life was scored using the Short Form 36 Health Survey before and after the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The current study results support the idea that peer-led exercise programs for aeging adults can lead to physical function improvements. Like previous studies [ 10 , 20 , 21 ], the drop-out rate for this program was meagre with a relatively high attendance rate. The combination of low drop-out rates and significant physical function improvements suggests that peer-led exercise programs are a successful intervention for ageing adults living in the community.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The current study results support the idea that peer-led exercise programs for aeging adults can lead to physical function improvements. Like previous studies [ 10 , 20 , 21 ], the drop-out rate for this program was meagre with a relatively high attendance rate. The combination of low drop-out rates and significant physical function improvements suggests that peer-led exercise programs are a successful intervention for ageing adults living in the community.…”
Section: Discussionsupporting
confidence: 58%
“…Participants in the intervention also reported a more significant improvement in general health, more energy, and fewer role limitations due to emotional problems than those in the control group. A study conducted with 78 ageing adults who participated in a peer-led exercise program also reported an improvement in many domains of the SF-36 despite high baseline scores [ 21 ]. According to previous studies, a greater sense of self-efficacy arising from peer-led exercise could, in part, explain a change in health perceptions [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, five papers published findings from the same study which explored the impact of a home-based physical and nutritional intervention on various outcome measures [ 19 23 ]. Eight studies were included in the narrative analysis, which included three randomised controlled trials [ 22 , 24 , 25 ], two quasi-experimental studies [ 26 , 27 ], a large prospective cohort study [ 28 ], an observational study [ 29 ] and a single group repeated measure design study [ 30 ]. Six studies were conducted among older people who were living at home, one study included older people in assisted living facilities [ 26 ] and one study included nursing home residents [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Volunteer leadership of programs may enhance sustainability and reach (24,39,51,52). Community-based program sustainability is important to make long-term differences in health behaviors, which is vital for rural older adults who are less healthy and more sedentary than their urban counterparts (53,54).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have compared volunteer-led groups and a control group, but few reported functional fitness outcomes and drew comparisons between volunteer-led and professionally-led approaches in real-world, community-based settings (26,33,35,52). The study described here examined fitness improvements among participants of two types: those in counties adopting a volunteer-led program model, and those relying solely on an educator-led model for StrongWomen Program (SWP) delivery.…”
Section: Literature Reviewmentioning
confidence: 99%